Analyses of long-term measurements (2005-2012) of 7Be concentrations in surface air aerosols - Pérez-Martínez, Manuel; Dueñas-Buey, Mª Concepción; Fernández, Mª Carmen; Liger-Pérez, Esperanza; Gordo Puertas, Elisa; Cañete-Hidalgo, Sergio Andrés (EAC_2013, 2013)
Studies of radionuclide activities in aerosol particles provide a mean for evaluating the integrated effects of transport and meteorology on the atmospheric loadings of substances with different sources. The aim of the present study is to explain the behaviour of aerosols associated with 7Be (T1/2=53.3 days) in the surface atmosphere using exploratory data analysis to obtain information on their possible mechanisms of transport and deposition. This naturally occurring radionuclide is an important isotope in studying atmospheric processes because of its convenient half-life and sufficiently detectable -radiation (E = 0.477 MeV), which has served for studying precipitation scavenging, vertical and horizontal removal of air masses, aerosol transit and residence times in the troposphere [1].
Keywords: Isótopos radiactivos; Aerosoles atmosféricos; long-term measurements; Be-7